Um estudo sobre escolhas léxico-gramaticais de duas professoras de inglês em um diário dialogado - Rocha, Sabrina da Costa (2009)
Situated in the field of Applied Linguistics, this case study focuses on a dialogue journal and addresses issues such as reflective teacher development (PIMENTA & GHEDIN, 2002; ZEICHNER, 2002), the teacher-researcher (FREEMAN, 1996; LÜDKE, 2001), and journal writing as a possibility for teachers to (re)interpret and (re)evaluate their own discursive practices (LIBERALI, 1999; REICHMANN, 2001; ZABALZA, 2004, amongst others). In the light of these considerations, this case study focuses on a reflective dialogue journal produced over five months by two EFL public school teachers in northeastern Brazil, in 2007. The study aims at investigating how the teachers make meaning of their own experiences, that is, how they represent their practice in the fourteen selected narratives through their lexical-grammatical choices. Taking into account that discourse is a practice of signifying the world (FAIRCLOUGH, 1992), and on adopting Systemic-Functional Grammar (HALLIDAY, 1994) as the theoretical framework grounding this study, more specifically, the transitivity system, the main objective of this study is to examine the representation of teaching experience through Processes and Participants (HALLIDAY, 1994) in 126 primary clauses and in 29 projected clauses. Results reveal that Beatriz´ experience is mainly represented by mental Processes, while Clarisse‟s experience is represented mostly by relationals. It can be seen that Beatriz problematizes her own practice, questioning, while Clarisse characterizes and compares their practices, counseling. As to the mental projections, teachers´ representations are constituted by material and relational Processes, indicating doing and being in terms of challenges and (dis)pleasures regarding the classroom and the profession. In sum, on giving visibility to language teachers´ work, research practice, and to collaborative construction of knowledge, this study is a contribution to EFL continued teacher development.